Journal article review by Rhodes Muyunda Motivation and cultural correlates of second language acquisition: An investigation of international students in the universities of the People’s Republic of China, - Watkins, David A.; Yu, Baohua (IJRDO- Journal of Educational Research, 2016)
The researchers noted that it should be the teachers’ responsibility to ensure that their learners are not only integratively motivated inside the classroom but also outside. This is apparently due to the fact that integrativeness helps to enhance students’ willingness to learn an L2. Furthermore, universities should come up with ways to help students at intermediate level of studying Chinese since this stage was sought to be problematic for the students. This can be done by developing a Chinese language curriculum for with more engaging activities and themes that learners have interest in. Teachers of Chinese language should also be educated about certain features of Asian students that hinder their L2 learning. This will help the teachers to come up with ways of helping them.